Prognostic Significance of NOTCH1 and FBXW7 Mutations in Pediatric T-ALL. Issue 6 (30th May 2013) - Erbilgin, Yucel; Sayitoglu, Muge; Hatirnaz, Ozden; Dogru, Omer; Akcay, Arzu; Tuysuz, Gulen; Celkan, Tiraje; Aydogan, Gonul; Salcioglu, Zafer; Timur, Cetin; Yuksel-Soycan, Lebriz; Ure, Umit; et al.
Abstract : The NOTCH signaling pathway plays important role in the development of multicellular organisms, as it regulates cell proliferation, survival, and differentiation. In adults, it is essential for the T- or B-lymphocyte lineage commitment. NOTCH1 and FBXW7 mutations both lead the activation of the NOTCH1 pathway and are found in the majority of T-ALL patients. In this study, the mutation analysis of NOTCH1 and FBXW7 genes was performed in 87 pediatric T-ALLs who were treated on the ALL-BFM protocols. In 19 patients (22%), activating NOTCH1 mutations were observed either in the heterodimerization domain or in the PEST domain and 7 cases (10%) demonstrated FBXW7 mutations (2 cases had both NOTCH1 and FBXW7 mutations). We also analyzed the relationship of the mutation data between the clinical and biological data of the patients. NOTCH1 and FBXW7, NOTCH1 alone were found correlated with lower initial leucocyte counts which was independent from the sex and T- cell immunophenotype. However, NOTCH1 and FBXW7 mutations were not predictive of outcome in the overall cohort of pediatric T-ALLs.